Understanding Contextual Strategies and Engaging Learning from SMA NW Kopang Biology Teacher to Enhance Student Motivation - Sakaroni, Rubiyatna; Listantia, Nora; Ningthias, Dyah Puspitasari (Yayasan Pendidikan Insan Mulia Utan Sumbawa, 2025)
Challenges in learning biology often arise, especially due to the complex nature of the material and requires a deep understanding of interrelated concepts. This causes many students to experience decreased motivation. The biology teacher of SMA NW Kopang keeps students motivated in learning. This study aims to understand the strategies applied by biology teachers at SMA NW Kopang in increasing students' learning motivation. This research uses a qualitative approach with the methods of observation, in-depth interviews, and document analysis. The research findings show that teachers use various strategies such as contextual learning, the use of educational technology, personalised approaches, as well as the insertion of ice breaking and rewards to create an interactive and relevant learning atmosphere. In addition, the integration of Islamic values in biology learning provides a moral dimension that strengthens the relationship between science and student character. Internal factors such as student interest and confidence, as well as external factors such as teacher support and learning environment, were found to have a significant influence on learning motivation. These strategies not only help students understand complex biological material, but also encourage their active involvement in learning. This research contributes to the development of learning methods that are innovative and relevant to students' needs, particularly in Islamic-based schools. Further research is recommended to explore the long-term impact of these strategies on students' learning outcomes across different educational contexts.